2005
DOI: 10.1038/sj.leu.2403665
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death – other than progressive leukemia – in childhood acute lymphoblastic (ALL) and myeloid leukemia (AML): the Dutch Childhood Oncology Group experience

Abstract: We analyzed causes of death, other than resistant disease or relapse, in 875 children with acute lymphoblastic leukemia (ALL) and 229 with acute myeloid leukemia (AML), treated on three different Dutch Childhood Oncology Group (DCOG) ALL and three AML protocols. Overall, 23 (2.6%) ALL and 44 (19.2%) AML patients died. Early death (ED, before remission was reached) occurred in nine ALL (1%) and thirty AML (13.1.%) patients, including three and ten deaths before treatment was initiated. Chemotherapy-related mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
100
4
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 36 publications
8
100
4
5
Order By: Relevance
“…Death in complete remission was defined as any death occurring 42 days or later after diagnosis in patients who achieved remission. These definitions are consistent with those used by others (Christensen et al, 2005;Slats et al, 2005) to facilitate future comparisons across studies.…”
Section: Outcome Measuressupporting
confidence: 61%
See 3 more Smart Citations
“…Death in complete remission was defined as any death occurring 42 days or later after diagnosis in patients who achieved remission. These definitions are consistent with those used by others (Christensen et al, 2005;Slats et al, 2005) to facilitate future comparisons across studies.…”
Section: Outcome Measuressupporting
confidence: 61%
“…However, our report is the first to compare the relative contribution of TRM with treatment failure for children with ALL and AML in an LIC. In HICs, TRM accounts for more treatment failure in children with AML than ALL (Christensen et al, 2005;Ravindranath et al, 2005;Slats et al, 2005;Creutzig et al, 2006;Pui and Evans, 2006). Our finding suggests that in LICs, efforts to reduce TRM are as important for children with ALL as for those with AML.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…More recently, therapy optimization focusses on asparaginase, including asparaginase dose intensification, therapeutic drug monitoring, and the use of novel pegylated formulations, as reviewed by Pieters et al 8 The progress made with these changes are not yet visible in the results reported by Gatta et al as these developments are too recent. At least as important are the improvements in supportive care reducing the number of patients dying from treatment-related mortality, 9 including developments in blood-banking, antibiotics and antifungals, parenteral nutrition and tumor lysis prevention.…”
mentioning
confidence: 99%